Analysis of Ergonomic Factors in Carpentry Activities: Application of a System for Comparing Productive Movement Patterns and Fatigue - Figueiredo , Symone; Cruz, Felipe Mendes da; Guimarães, Bruno Maia de; Rocha , Eudes Arimatéa; Lago, Eliane Maria Gorga (National Journal of City Management, 2026)
Objective - to assess the impacts of ergonomic factors on health and productivity in the activities of carpenters in the construction industry. Methodology - The study adopted a quantitative-qualitative approach, with an exploratory bias in order to compare productive movement patterns with movement patterns associated with fatigue, using innovative methods such as Kinobot software for movement monitoring and the Bipolar Pain Questionnaire for fatigue assessment, in addition to a form for surveying the profile of workers with a sample of 15 participants, relating ergonomic factors to productivity in daily activities. Originality/relevance – The theoretical gap is the correlation of ergonomic factors with the analysis of movement patterns using Kinobot software to verify these movements and their correlations with productivity. Results – Regarding the Systematic Literature Review, it was noted that there are few studies that relate ergonomics and productivity applied to construction sites. It was found that issues such as climate change, the phase of the work with stages in completion presenting a slower work pace, and fatigue can interfere with the development of activities. It was noted that the different periods of the works should be considered, as they become a determining factor for the perception of fatigue. Theoretical/methodological contributions – although there are studies that abo methodological issues, in addition to the application of questionnaires in stages to identify ergonomic factors, their application and interfaces with productivity represent a differential. Social and environmental contributions – From a social perspective, this study is relevant because it contributes to improving working conditions, promoting the physical and psychological well-being of construction workers. In addition, reducing fatigue and increasing efficiency can generate significant economic benefits for both workers and companies in the sector and, in turn, environmental contributions through better management and use of resources to meet the Sustainable Development Goals.